Macro mineral requirements by grazing zebu bovines - Moraes, Eduardo Henrique Bevitori Kling de; Paulino, Mário Fonseca; Moraes, Kamila Andreatta Kling de; Valadares Filho, Sebastião de Campos; Lazzarini, Isis; Monnerat, João Paulo Ismério dos Santos; Couto, Victor Rezende Moreira; Souza, Marcos Gonçalves de [UNESP] (Sociedade Brasileira de Zootecnia, 2012)
The objective of this study was to determine requirements of calcium (Ca), phosphorus (P), magnesium (Mg), potassium (K) and sodium (Na) for grazing zebu bovines. The experiment area was composed of Brachiaria decumbens paddocks. Twenty-seven non-castrated animals, with initial live weight of 311.0 kg and at an average age of 14 months were used. Three animals were slaughtered, after adaptation period, so they were used as control for estimates of empty body weight and initial body composition of animals in the experiment. Out of the 24 remaining animals, four were sent to the maintenance group with restrict grazing time to limit energy intake close to the maintenance level. The other 20 animals were distributed in four treatments: mineral mixture, self-control intake and three-times-a-week-offer frequency (offered on Mondays, Wednesdays and Fridays) and daily. Concentrations of all studied macro elements in empty body and empty body gain decreased as live weight increased. The ratios obtained for g Ca/100 g of retained protein and g P/100 g of retained protein were 9.18 and 4.72, respectively. Total dietary requirement of calcium was lower than the one recommended by NRC (2000), but P requirement was very close to that.
Keywords: macro minerals; pasture; requirement; zebu cattle